Prelicensure Nursing Student Perceptions of Replacing Traditional Clinical Hours With Simulation - Stephanie Dunn; Jill Johnson; Natalie Persson (Nurse Educator, 2026)
Background: The National Council of State Boards of Nursing recommends that high-quality simulation can replace up to 50% of traditional clinical hours; yet, little is known about nursing students’ perceptions of this guideline. Purpose: This study explored student perceptions of replacing traditional clinical hours with simulation to inform curriculum planning and clinical education. Method: A descriptive cross-sectional survey examined students’ understanding and perceptions of simulation as a replacement for traditional clinical hours. Quantitative findings and qualitative responses were considered together to identify patterns in students’ perceptions. Results: Most students supported limited to moderate replacement of traditional clinical hours with simulation. Reported advantages included improved clinical judgment and reflection, efficiency, a controlled learning environment, and targeted skill development. Disadvantages included a lack of authenticity, limited professional identity development, and performance anxiety. Conclusion: Student perceptions suggest that simulation and traditional clinical experiences each contribute unique learning opportunities, supporting the integration of both throughout the nursing curriculum.